Avalia????o do impacto da qualidade de servi??os na lealdade dos consumidores de materiais para constru????o civil : aplica????o dos modelos SERVQUAL e RSQ em homecenters paulistanos - Lopes, Evandro Luiz (2007)
There is no doubt about the importance of the services sector in the national economy scene. Data released by IBGE - Instituto Brasileiro de Geografia e Estat??stica (Brazilian Instituteof Geography and Statiscs), show that this industry was responsible for 53,6% of Gross Domestic Product in 2004, and employing approximately 56% of current active workforce. It is also evident the importance of the retailers in the services sector composition, which in 2004 was responsible for handled more than R$ 330 billion in business. Notably in the very last few years, this economy sector has become high competitive, on one hand by national and the professionalism of the operations on the other hand by the entries of new international players. Given this scenario, this research suggests studying the services quality management in the retailers environment and its relationship with customers loyalty to the point of sales. The survey of field information collected 500 customers of a homecenters chain that were analysed using statistical multivariated techniques, such as factorial analysis, linear regression and structural equations modeling, seeking to stablish the relevance between services quality and customer loyalty. The theoretical fundamental framework was based on two quality services models - the SERVQUAL model and the Retail Service Quality model. Among observed results it was found that services quality perceived explain 65% of variance of loyalty behavior the sample, being the Retail Service Quality model the most aproprieted for this type of analysis.